(untitled) (Research, Society and Development, 2023)
The Covid-19 pandemic has brought numerous challenges to education globally. The large amount of changes required teachers, schools, students and families to adapt quickly, changing the way of learning and teaching even after the pandemic period. This work aimed to discuss some factors related to education after the Covid-19 pandemic crisis. The methodology used is a systematic review of the literature. From the findings, it was observed that technology came in a permanent way, that is, even after the pandemic, tools such as google meet, among others, will be used continuously. Teachers and students began to use technology more frequently, becoming increasingly familiar with different types of tools. However, it is necessary to raise an alert so that post-pandemic teaching maintains some fundamental characteristics, such as, for example, considering the student as the protagonist in their own development, so that they can learn to better deal with these tools in an autonomous way, being the teacher responsible for guiding him on his path.